Plan estratégico de comunicación enfocado a la motivación de los funcionarios del Cuerpo de Bomberos de Macas - Montenegro Calle, Karla Dayana (2014)
The proposal of this thesis was given in reality observed in the Institution of Macas Fire Department, where there are high ideals of human survival and growth of its work is necessary, with the preparation of the Strategic Planning from the Communication. This investigative process required finding errors in corporate communication, posing at first the different theories that support the way of strategies and conceptualizations in the internal, external communication from its applicability. Besides the results were established which defined the product obtained with the technical studies, which showed the Institutional Tissue of Fire Department, then it´s given the sequence of Workshop of Communicative Diagnosis applied to paid staff, where the analysis FODA is shown. Results were born, and therefore the Strategic Communication Plan, using communication as a tool for institutional growth. We conclude, to be made a planned communication from internal and external institutional reality.